How antagonistic salts cause nematic ordering and behave like diblock copolymers - Jung, Wieland David Krischan; Rivas, Nicolas; Harting, Jens (Journal of Chemical Physics, 2019)
We present simulation results and an explanatory theory on how antagonistic salts affect the spinodal decomposition of binary fluid mixtures. We find that spinodal decomposition is arrested and complex structures form only when electrostatic ion-ion interactions are small. In this case, the fluid and ion concentrations couple and the charge field can be approximated as a polynomial function of the relative fluid concentrations alone. When the solvation energy associated with transferring an ion from one fluid phase to the other is of the order of a few kBT, the coupled fluid and charge fields evolve according to the Ohta-Kawasaki free energy functional. This allows us to accurately predict structure sizes and reduce the parameter space to two dimensionless numbers. The lamellar structures induced by the presence of the antagonistic salt in our simulations exhibit a high degree of nematic ordering and the growth of ordered domains over time follows a power law. This power law carries a time exponent proportional to the salt concentration. We qualitatively reproduce and interpret neutron scattering data from previous experiments of similar systems. The dissolution of structures at high salt concentrations observed in these experiments agrees with our simulations, and we explain it as the result of a vanishing surface tension due to electrostatic contributions. We conclude by presenting 3D results showing the same morphologies as predicted by the Ohta-Kawasaki model as a function of volume fraction and suggesting that our findings from 2D systems remain valid in 3D.
CRIS-Team WoS Importer:2019-03-06

Monolayer Structures of Supramolecular Antagonistic Salt Aggregates - Jung, Wieland David Krischan; Harting, Jens; Sega, Marcello (Journal of Physical Chemistry B, 2021)
The speculated presence of monomolecular lamellae of antagonistic salts in oil-water mixtures has left several open questions besides their hypothetical existence, including their microscopic structure and stabilization mechanism. Here, we simulate the spontaneous formation of supramolecular aggregates of the antagonistic salt sodium tetraphenylborate (NaBPh4) in water and 3-methylpyridine (3-MP) at the atomistic level. We show that, indeed, the lamellae are formed by a monomolecular layer of the anion, enveloped by 3-MP and hydrated sodium counterions. To understand which thermodynamic forces drive the aggregation, we compare the full-atomistic model with a simplified one for the salt and show that the strong hydrophobic effect granted by the large excluded volume of the anion, together with electrostatic repulsion, suffice to explain the stability of the monomolecular lamellae.
CRIS-Team Scopus Importer:2021-04-09

Probing sedimentation non-ideality of particulate systems using analytical centrifugation - Uttinger, Maximilian; Jung, Wieland David Krischan; Dao, Thi Quynh Nhi; Canziani, Herbert; Lübbert, Christian; Vogel, Nicolas; Peukert, Wolfgang; Harting, Jens; Walter, Johannes (Soft Matter, 2021)
Analytical centrifugation is a versatile technique for the quantitative characterization of colloidal systems including colloidal stability. The recent developments in data acquisition and evaluation allow the accurate determination of particle size, shape anisotropy and particle density. High precision analytical centrifugation is in particular suited for the study of particle interactions and concentration-dependent sedimentation coefficients. We present a holistic approach for the quantitative determination of sedimentation non-ideality via analytical centrifugation for polydisperse, plain and amino-functionalized silica particles spanning over one order of magnitude in particle size between 100 nm and 1200 nm. These systems typically behave as neutral hard spheres as predicted by auxiliary lattice Boltzmann simulations. The extent of electrostatic interactions and their impact on sedimentation non-ideality can be quantified by the repulsion range, which is the ratio of the Debye length and the average interparticle distance. Experimental access to the repulsion range is provided through conductivity measurements. With the experimental repulsion range at hand, we estimate the effect of polydispersity on concentration-dependent sedimentation properties through a combination of lattice Boltzmann and Brownian dynamics simulations. Finally, we determine the concentration-dependent sedimentation properties of charge-stabilized, fluorescently-labeled silica particles with a nominal particle size of 30 nm and reduced interparticle distance, hence an elevated repulsion range. Overall, our results demonstrate how the influence of hard-sphere type and electrostatic interactions can be quantified when probing sedimentation non-ideality of particulate systems using analytical centrifugation even for systems exhibiting moderate sample heterogeneity and complex interactions.<br

The Impact of Rate Formulations on Stochastic Molecular Motor Dynamics - Blackwell, Robert; Jung, Wieland David Krischan; Bukenberger, M.; Smith, Ana-Suncana (Scientific Reports, 2019)
Cells are complex structures which require considerable amounts of organization via transport of large intracellular cargo. While passive diffusion is often sufficiently fast for the transport of smaller cargo, active transport is necessary to organize large structures on the short timescales necessary for biological function. The main mechanism of this transport is by cargo attachment to motors which walk in a directed fashion along intracellular filaments. There are a number of models which seek to describe the motion of motors with attached cargo, from detailed microscopic to coarse phenomenological descriptions. We focus on the intermediate-detailed discrete stochastic hopping models, and explore how cargo transport changes depending on the number of motors, motor interaction, system constraints and rate formulations, which are derived from common thermodynamic assumptions. We find that, despite obeying the same detailed balance constraint, the choice of rate formulation considerably affects the characteristics of the overall motion of the system, with one rate formulation exhibiting novel behavior of loaded motor groups moving faster than a single unloaded motor.
CRIS-Team Scopus Importer:2019-12-20